Effects of Acetylsalicylic Acid on Human Platelet Function In Vivo at Salicylate Steady State - Simrock, R; Missalla, A; Schwidtal, P; Lischke, V; Breddin, H K (Thrombosis and Haemostasis, 1984)
The results of clinical trials concerning the use of acetylsalicylic acid (ASA) as antithrombotic drug are contradictory. Inhibition by ASA of platelet prostaglandin synthesis and aggregation is prevented by its metabolite salicylic acid (SA) in animals and in human platelets in vitro. It was suggested that ASA might produce its own inhibitor, thereby diminishing its efficiency in thromboembolic disease.In four healthy male subjects there was no difference in inhibition of collagen-induced platelet aggregation after the administration of 500 mg ASA alone or at salicylate steady state (3 g SA daily). But the inhibition of tissue-extract-induced platelet shape change was diminished and shortened by pretreatment with SA. We conclude that SA does not inhibit the effects of ASA on human platelet aggregation in vivo in therapeutic dose ranges. The clinical importance of the SA/ASA-interaction on tissue-extract-induced platelet shape change remains to be clarified.
Keywords: Platelet function; Acetylsalicylic acid; Salicylate steady state; Salicylic acid/acetylsalicylic acid-interaction